2012
DOI: 10.1002/jbm.a.34123
|View full text |Cite
|
Sign up to set email alerts
|

Experimental model of biofilm implant‐related osteomyelitis to test combination biomaterials using biofilms as initial inocula

Abstract: Currently, the majority of animal models that are used to study biofilm‐related infections use planktonic bacterial cells as initial inocula to produce positive signals of infection in biomaterials studies. However, the use of planktonic cells has potentially led to inconsistent results in infection outcomes. In this study, well‐established biofilms of methicillin‐resistant Staphylococcus aureus were grown and used as initial inocula in an animal model of a Type IIIB open fracture. The goal of the work was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…First, our previously published studies have indicated that the MRSA isolate used in this study produces biofilms on PEEK material [19][20][21][22]. Second, PEEK is commonly used in spinal implant surgeries and these data may provide an indication of MRSA biofilm formation on PEEK materials that may be relevant to other clinical applications.…”
Section: Materials and Machiningmentioning
confidence: 88%
See 2 more Smart Citations
“…First, our previously published studies have indicated that the MRSA isolate used in this study produces biofilms on PEEK material [19][20][21][22]. Second, PEEK is commonly used in spinal implant surgeries and these data may provide an indication of MRSA biofilm formation on PEEK materials that may be relevant to other clinical applications.…”
Section: Materials and Machiningmentioning
confidence: 88%
“…It was collected from the knee of an infected patient who underwent arthroscopic surgery and was kindly provided by ARUP Laboratories (Salt Lake City, UT, USA). This isolate has been confirmed to contain the icaADBC gene operon and has been used in previous studies to confirm its pathogenic and biofilm-forming properties [19,21,22]. The isolate was stored at À80°C and passaged fewer than two times on Columbia blood agar (Hardy Diagnostics, Midvale, UT, USA) before each use.…”
Section: Bacterial Isolatementioning
confidence: 99%
See 1 more Smart Citation
“…Williams et al recently published a model simulating type IIIB Gustilo open fracture using the proximal part of the tibia of sheep (Williams et al , 2012b). They used two 2.0 × 2.0 cm metal plates separated by 1.0 cm that could accommodate a membrane that was coated with a MRSA biofilm.…”
Section: Literature Review Of Animal Modelsmentioning
confidence: 99%
“…The in vitro data that were generated and the CSA-13 coating itself were translated to a sheep model of a simulated Type IIIB open fracture [52]. The method by which infection was caused in the sheep model of this study was to first grow well-established biofilms of MRSA in a membrane biofilm reactor [53,54].…”
Section: Introductionmentioning
confidence: 99%